Corpos infantis que “não cabem” na escola : os discursos de professoras nos protocolos de encaminhamento ao setor de psicologia - Stefani Neto, Danilo Flávio (2017)
The need for therapies, reports and interventions on children referred by the school for suspicion of attention disorder, concentration difficulties, emotional unrest, behavior problems and problems in relationships with peers finds in the Psychology Service the possibility of producing speeches as a way to refer the failure, ending it in the own child. This research, belonging to the Research Group “Infância, Juventude e Cultura Contemporânea” – GEIJC - ("Childhood, Youth and Contemporary Culture"), parts of the following question: which discourses about the children's bodies compose the complaints presented in the protocols, made by teachers of the municipal public education department of Sorriso city, Mato Grosso state, to the Psychology Service? The main objective of this study is to analyze the teachers' discourses about the bodies of the children in the forms to the psychologists, intending to understand the needs of “psychological” intervention, highlighting the reasons and the agents in the discursive net that request it (teachers, pedagogical coordinators or counselor, parents, school community).As specific objectives, we seek to: characterize the "psychological" demands of schools, based on protocols´ complaints enunciated by educators; To investigate the causes and differences in the needs for psychological intervention with children, based on gender relations in the school context and in the ways in which the teachers conceive them; To demarcate, in the teachers' discourses, what constitutes the "child ideal body", adapted to their education, development and learning. Based on dichotomous conceptions about the education and development of children, the teacher who directs these children seeks, through the expectations assigned to the practice of Psychology, for therapies, interventions, observations and evaluations that contribute to the “pedagogical teach” in classroom. The emergence of the "individual person" that doesn´t concerns in the space supported by essentially biological visions on the child, or in a maturation perspective of deficits and neuropsychological delays, sometimes related to the lack of will, motivation or interest, foments the tendency to solve these conflicts in outer space beyond the school. With a qualitative approach, the research is divided into three stages: the first corresponds to the analysis, tabulation and organization of protocol data sent from municipal school units throughout the academic year of 2015; The second, to the analysis and categorization of the complaints described by teachers; The third one, the interviews with six teachers (two from each phase - Early Childhood Education, Elementary School up to 5th year and Elementary School after the 6th year). Based on concepts of dialogism, ideology, responsiveness and genres of discourse for Bakhtin, it is proposed to analyze the ideologies present in school complaints, also considering authors such as Le Breton, Vigotski and Foucault. The analysis of the referral protocols and the interviews evidences distinctions in the characterization of the educational problems between boys and girls present in the complaints of their teachers. As a responsive act in the chain of productions on the theme, this research tries to contribute to the debates on the "unmedicalization" and non-pathologization of contemporary childhood.